Kepemimpinan Sandwich di Tengah Tantangan Digitalisasi dan Solusinya dalam Pengelolaan Gereja - Martha Mulyani Kurniawan (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
This study aims to analyse the phenomenon of sandwich leadership in church ministry, identify the main challenges faced, and offer relevant solutions in the digital age. The method used is a descriptive-qualitative approach through literature review and phenomenological observation, so that the focus of the study is directed at a deep understanding of the meaning of the phenomenon. The results show that sandwich leaders face three main issues, namely difficulties in establishing effective two-way communication, differences in views between the digital and non-digital generations, and pressure in managing multidimensional ministries. To address these challenges, this study offers several strategic solutions. First, the application of a transformational leadership style that emphasises vision, inspiration, and empowerment of congregations across generations. Second, improving digital literacy for leaders and congregations as a means of strengthening service effectiveness. Third, establishing a collaborative service system that can bridge generational differences without neglecting the essence of the Christian faith.